Pengawasan Dan Ketersediaan Peralatan Kerja Unit Apron Movement Control Di Area Airside Bandar Udara H. Hasan Aroeboesman Ende - Redemptus Etriko Mbete Bhoka; Sri Sutarwati (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The AMC unit is a unit responsible for regulations, supervision of aircraft movements, traffic of vehicles, people and goods as well as cleanliness in airside areas, aviation records so that aviation security and safety can be achieved. In carrying out the duties and responsibilities of the AMC unit, complete supporting equipment is required, such as Follow Me Car, Safety Vest, Ear Muff, Handy Talky, VHF Radio, PABX, Binoculars, Speed Gun and Computer. The AMC unit at H. Hasan Aroeboesman Ende Airport in carrying out surveillance in the airside area has not been equipped with adequate equipment in accordance with the SOP. This research aims to find out how the AMC unit's work equipment is monitored and available, the constraints of AMC officers and what the flow of infrastructure procurement is.This research uses a descriptive qualitative approach. The data used are primary and secondary data. Primary data was obtained from observations and interviews, while secondary data came from SOPs, photos and regulations related to the problems studied. The data analysis techniques used are data reduction, data presentation and drawing conclusions. To test the validity of the data, triangulation techniques were used. The results of this research show that the Apron Movement Control (AMC) unit at H. Hasan Aroeboesman Ende Airport has carried out its duties in accordance with the Standard Operating Procedure (SOP) and General Civil Aviation Regulation Number KP 038 of 2017 concerning Apron Management Service. Supervision in the apron area has been carried out effectively by carrying out inspections from 06.00 - 18.00 WITA in the morning. The obstacles for AMC officers in carrying out their duties are that there is no Follow Me Car to be used for monitoring and inspections and there is no Radio Base available so all communication is carried out using Handy Talky. The flow of procurement of work equipment for the AMC unit at H. Hasan Aroeboesman Ende Airport begins with making a Note/Equipment Requirement, then the Head of the AMC Unit proposes the procurement of equipment to the Service and Cooperation Section, after approval, the letter is submitted to the Head of the Administration Sub-Division, then handed over to the Head of UPBU Airport H. Hasan Aroeboesman, Financial Manager and Expenditure Treasurer.